The Automatic Exhibition: Slide Shows and Electronics at the Swiss National Exhibition 1964 - Lugon, Olivier (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2014)
The advent of projection in exhibitions in the early 1960s brought with it a new form of automatized exhibition. Its rise was part of a larger phenomenon of automation and of rationalization of informational processes in Western society, with the rise of electronics. The Swiss National Exhibition in Lausanne in 1964 offers a good example of this: slide shows and multi-screen projections were used to promote administrative automation and to foster a new market of exhibition machinery.